2010
DOI: 10.1515/revce.2010.002
|View full text |Cite
|
Sign up to set email alerts
|

Methane decomposition catalysts for COx-free hydrogen production

Abstract: Catalytic decomposition of methane into CO x -free hydrogen and carbon nanofibers has recently attracted much attention. The development of high-performance catalysts is essential for production of CO x -free hydrogen from methane. In this review we summarize the catalytic systems used for methane decomposition and compare catalysts with different active components and supports. According to the literature and our recent research results, Ni is the most active metal for methane decomposition and its catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 158 publications
1
10
0
Order By: Relevance
“…This finding is of prime importance economically because bimetallic precursors are much more expensive than their monometallic analogues. It has been proven that transition metals of Period 4, namely, cobalt, iron, and nickel, display the highest activities, but grant only a short catalyst duration . The same trend was observed for Co/Al 2 O 3 and Fe/Al 2 O 3 catalysts herein.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…This finding is of prime importance economically because bimetallic precursors are much more expensive than their monometallic analogues. It has been proven that transition metals of Period 4, namely, cobalt, iron, and nickel, display the highest activities, but grant only a short catalyst duration . The same trend was observed for Co/Al 2 O 3 and Fe/Al 2 O 3 catalysts herein.…”
Section: Resultssupporting
confidence: 79%
“…The accessibility of the metal surface for hydrocarbon molecules has been regarded as a highly important factor that determines catalytic decomposition activity . In general, it has been reported that a direct correlation may be observed between the electronegativity of the metal loaded on the catalyst and the catalytic activity for CDM reactions . The susceptibility of the interaction and adsorption of CH 4 molecules by metal species increases with increasing electronegativity of metals .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] Additionally, a review article of Choudhary et al gives more details on the nonoxidative activation of CH 4 . [15][16][17][18][19][20] Additionally, a review article of Choudhary et al gives more details on the nonoxidative activation of CH 4 .…”
Section: Reactions With Methane Onlymentioning
confidence: 99%
“…152, 153 Diefenbach et al combined experiments in the gas phase on reactions of Pt þ with NH 3 , CH 4 , and CH 3 NH 2 in a Fourier transform ion cyclotron resonance mass spectrometer with theoretical studies. 156 In the Andrussow process, originally developed by BASF, the feed gas mixture contains additional O 2 to burn the H 2 , resulting in an exothermic reaction, as shown in eqn [18]. CH 4 is thought to be dehydrogenated over Pt to a carbene species, which then react with NH 3 from the gas phase to an intermediate species with a C-N bond.…”
Section: Reactions With Other Hydrocarbonsmentioning
confidence: 99%